2006
DOI: 10.2190/1g67-hll5-4172-083u
|View full text |Cite
|
Sign up to set email alerts
|

Online Study Groups: Reciprocal Peer Questioning versus Mnemonic Devices

Abstract: One hundred sixty students in an educational psychology course used WebCT Discussions to satisfy one of two study group conditions, reciprocal peer questioning or mnemonic devices. Students made postings according to their assigned study strategy in order to facilitate the learning of their group. At the end of the academic term, student permission was obtained to use three types of data for purposes of the investigation: 1) course grades; 2) WebCT records; and 3) rating scale responses that assessed personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Despite limited evidence of their effectiveness (Johnson, 2006b), web-based peer study groups are increasingly available to college students (Shale, 2002;Tait & Mills, 2003). Reportedly, 72% of American institutes of higher education provide some form of web-based peer tutoring (Miller & Lu, 2003).…”
mentioning
confidence: 99%
“…Despite limited evidence of their effectiveness (Johnson, 2006b), web-based peer study groups are increasingly available to college students (Shale, 2002;Tait & Mills, 2003). Reportedly, 72% of American institutes of higher education provide some form of web-based peer tutoring (Miller & Lu, 2003).…”
mentioning
confidence: 99%
“…Thus, group study may help encourage students to use active, deep, desirably difficult strategies for learning; as a corollary, students in group settings may be less tempted to use nonelaborative strategies that may seem obvious (and easy) when they are alone (e.g., rereading and underlining). Indeed, prior research on specific study strategies reported during structured group learning sessions indicates the use of the types of active strategies reported in the current study (Johnson, 2006;Sawyer & Berson, 2004).…”
Section: Discussionmentioning
confidence: 68%
“…Group study may also enhance deep thinking via enhanced verbalization of thoughts, ideas, and strategies (Girash, 2014). Research focusing on learning strategies in structured group study sessions has suggested that students use discussion, testing, and mnemonic devices (Johnson, 2006), as well as dual-coding, self-referencing, and paraphrasing (Sawyer & Berson, 2004). There is, however, limited research toward a general understanding of which strategies are typically chosen by undergraduates in a broader array of group settings; and further, which strategies are correlated with academic performance.…”
Section: Learning Strategies In Individuals and Groupsmentioning
confidence: 99%
See 1 more Smart Citation